Association between oral health-related quality of life and nutritional status among older adults in district of Kuala Pilah, Malaysia - Chan, Yoke Mun; Rosli, Tanti Irawati; Tengku Abdul Hamid, Tengku Aizan; Abdul Kadir, Rahimah (BioMed Central, 2019)
Background: Poor oral health has an impact on food choices and intake of important nutrients among older population. The use of oral health-related quality of life instruments along with the clinical dental indicators can help to assess the oral problems that lead to nutritional problems in this group. This study aims to determine the association between oral health-related quality of life (OHRQoL) and nutritional status among a group of older adults in Kuala Pilah district, Malaysia. Methods: A cross-sectional study was carried out on 446 older adults aged 50 years and above from 20 randomly selected villages. Respondents were interviewed to collect information on their demographic characteristics and oral health perception, followed by physical examination to measure height, weight and body mass index (BMI) of respondents. The validated Malay version of General Oral Health Assessment Index (GOHAI) was used to measure OHRQoL. Results: About one-third (35.8%) of the respondents had normal BMI. Majority of the respondents were overweight (40.4%) and obese (19.9%), while only a small proportion was underweight (3.9%). Mean GOHAI score was 53.3 (SD = 4.7), indicating low perception of oral health. About 81.6% respondents had moderate to low perception of oral health. Logistic regression analysis showed a statistically significant association between the GOHAI and BMI scores (OR = 2.3; p < 0.01). Conclusions: Oral health-related quality of life was significantly associated with nutritional condition of respondents. Older adults with poor perception of their oral health were more likely to have unsatisfactory BMI compared to those who perceived their oral health to be good.